2022
DOI: 10.1039/d1na00740h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the activity and stability of carbon-supported platinum–gadolinium nanoalloys towards the oxygen reduction reaction

Abstract: The activity/stability towards the ORR of PtxGd/C nanoalloys has been enhanced by controlling the atmosphere during the dealloying process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In our previous contribution, we have reported that the formation of porous nanoarchitectures does not provide any activity/stability benefit . Therefore, we have avoided the formation of these undesirable structures through acidic wash under an inert atmosphere as we previously reported …”
Section: Results and Discussionmentioning
confidence: 74%
“…In our previous contribution, we have reported that the formation of porous nanoarchitectures does not provide any activity/stability benefit . Therefore, we have avoided the formation of these undesirable structures through acidic wash under an inert atmosphere as we previously reported …”
Section: Results and Discussionmentioning
confidence: 74%
“…In another recent report, Cavaliere et al provided a chemical synthesis approach via a carbodiimide complex route for Pt x Gd nanoparticles. They identified the optimal Pt to Gd ratio and the corresponding particle size and stated that a higher degree of crystallinity and a lesser degree of porosity is beneficial for the ORR performance. , Lower porosity being beneficial for the ORR activity is in line with inactive concave sites. However, since both the morphology and the degree of crystallinity led to optimal performance in the literature results, this conclusion needs to be taken cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of the ink formulation and the catalyst loading as well as the catalyst dealloying conditions are just some directions to be taken to further enhance this performance. Indeed, as already discussed, dealloying in inert atmosphere leads to higher ORR activity and stability of the nanoalloys, and minimizes the formation of porous nanostructures [39] …”
Section: Applications In Pemfc Cathodesmentioning
confidence: 72%
“…In fact, the gaseous environment in which the selective dissolution of Gd takes place has a great impact on the free corrosion potential (or open circuit potential, OCP) of a corroding system: the presence of oxygen creates a complex mixed OCP, which affects the selective dealloying kinetics [38] . Under this knowledge, the ORR activity and stability of the Pt 4.7 Gd/C electrocatalyst were enhanced by minimizing the formation of porous nanostructures through performing the dealloying process under an inert atmosphere [39] …”
Section: Pt‐rem Alloy Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation